Using mind-mapping to teach vocabulary communicatively for the 5th form students at a primary school in Ninh Binh Province = Sử dụng sơ đồ tư duy để dạy từ vựng theo đường hướng giao tiếp cho học sinh lớp 5 tại một trường tiểu học ở Ninh Bình. - Phạm, Thị Hường (2019)
In the study, I carried out an action research with the 5A students of Phu Loc Primary school. Data of this study were obtained from the results of questionnaires and from pre-test, while-test and post-test results. Two instruments for collecting the data were (1) questionnaires toward vocabulary learning before and after applying the mind -mapping in teaching vocabulary and (2) the pre-test and post- test.